Wind turbine rotor design under wind farm control laws. Issue 4 (September 2020) - Sartori, L; Fidelibus, P De; Cacciola, S; Croce, A
Abstract: In this work, we investigate the impact of different wind farm control techniques on the structural design of a 10MW reference wind turbine. Active wake mixing and wake redirection have been recently proposed as a way to reduce wake-turbine interference in a wind farm and both show potential for improving the overall power production. However, such controllers modify the dynamic behaviour of the individual turbine, so that a thorough assessment of the resulting loads and displacements becomes necessary. In fact, as most wind turbines are designed according to international standards, one or more structural constraints are active on the final design, meaning that an increase of the sizing loads, or deflections, would make necessary to modify the structural layout. To investigate these aspects, we compare three redesigns of the same rotor: the first is equipped with a standard controller, while the second and the third integrate different wind farm controllers. All the solutions are optimized with our in-house design tool so that the three configurations emerge from the same design process. Results are then compared in terms of ultimate and fatigue loads, displacements and blade mass.